The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsami.0c12165
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Tuning of Interlayer Coupling in Noncentrosymmetric 3R-MoS2 with an Electric Double Layer Interface

Abstract: Interlayer coupling in two-dimensional (2D) layered materials plays an important role in controlling their properties. 2H-and 3R-MoS 2 with different stacking orders and the resulting interlayer coupling have been recently discovered to have different band structures and a contrast behavior in valley physics. However, the role of carrier doping in interlayer coupling in 2D materials remains elusive. Here, based on the electric double layer interface, we demonstrated the experimental observation of carrier dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The lower intensity of S mode and obvious red shift of the LB mode indicate that the interlayer coupling of 0° bilayer MoS 2 is weaker than that of 60° bilayer MoS 2 . This is consistent with the previous report, which further confirms the sensitivity of LF Raman spectroscopy to probe the interlayer information.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The lower intensity of S mode and obvious red shift of the LB mode indicate that the interlayer coupling of 0° bilayer MoS 2 is weaker than that of 60° bilayer MoS 2 . This is consistent with the previous report, which further confirms the sensitivity of LF Raman spectroscopy to probe the interlayer information.…”
Section: Resultssupporting
confidence: 93%
“…For folded MoS 2 , the intensity of S mode is relatively weak and even disappears in most of the twist angles. This phenomenon is also observed in other reports and 2D materials, which can be attributed to the very weak interlayer shear coupling and the signals’ mergence into the background of the Rayleigh line. , The LB mode appears in all of the twist angles and we mainly focus on it. The frequency of the LB mode shows variation with different twist angles, and at the twist angle of 30.2°, there is an obvious red shift relative to other twist angles (Figure c).…”
Section: Resultssupporting
confidence: 76%
“…There were 10 fingers in our interdigital structure, 5 up and 5 down [35], and Figure 1b is a physical image of the detector. As a widely used non-damaged measurement, Raman spectroscopy could be used to investigate intralayer vibration modes, interlayer vibration modes, and the layer coupling in 2D materials effectively [36,37]. Figure 2 showed Raman curves of ZnO NWs, 2D Bi 2 Se 3 and Bi 2 Se 3 /ZnO NWAs.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Zhang et al revealed the effect of electric field on tuning the interlayer coupling of 2H and 3R phase MoS 2 . [105] It is suggested that electron doping could significantly enhance interlayer coupling, and the interlayer chemical bonds are susceptible to electron doping and tend to alter its lattice parameters. Therefore, it is reasonable to deduce that this phase conversion may be induced by the doped electron from the molten lithium salt with the raised temperature, the 3R phase MoS 2 may be emerged as the intermediate state between 2H and 1T phase, and the solid mechanisms are expected to be dug further.…”
Section: Alkali Ions Intercalation Methodsmentioning
confidence: 99%